Diseases of the sinuses : diagnosis and management - Kennedy, David W., 1948-; Bolger, William E.; Zinreich, S. James (Hamilton, Ont. ; Lewiston, N.Y. : B.C. Decker, Incorporated, 2001)
This is a collection of 33 chapters, each dealing with current aspects of diseases of the sinuses. The scope is comprehensive and includes areas of basic pathophysiology, diagnosis, and medical and surgical treatment. A majority of chapters cover technical aspects of sinus surgery. The purpose is to provide a comprehensive and current perspective on the diagnosis and medical and surgical care of rhinosinusitis. The field of rhinology has advanced rapidly in the last decade, especially in the area of surgical treatment. The editors intend to collect the most current and authoritative perspectives from experts around the world. This is a worthy objective as most textbooks in this field tend to have a more narrow perspective. The audience is otolaryngologists-head and neck surgeons, especially those with a focus in rhinology. Other specialists such as radiologists, pathologists, maxillofacial surgeons, ophthalmologists, neurosurgeons, and infectious disease specialists may also find this a useful reference. This is an appropriate audience, and physicians in practice as well as residents in training will find the book most useful. The authors are well respected authorities in their fields. This book brings together an impressive group of authors with significant expertise in the diagnosis and treatment of sinusitis. The majority of the material deals with up-to-date surgical evaluation and treatment. Routine as well as unusual disorders are included. Current understanding of basic pathophysiology is covered very well. The book features a CD-ROM with the full text and color pictures that is also searchable. Our understanding of sinusitis has progressed rapidly in the last decade. With this has come significant improvements in technology allowing for a more refined diagnosis and surgical treatment. This book collects the best of current knowledge from an international authorship focused on many of the critical areas of sinusitis diagnosis and management. The comprehensive and expert authorship make this book fairly unique, and it should be useful as a reference and source for continuing education and required reading for all otolaryngology residents. 0.93. David B. Conley, MD(Northwestern University Feinberg School of Medicine). Copyright 2016 Doody Reviews.
Contents r / S. James Zinreich, Thaddaeus Gotwald r / Pontus L. E. Stierna r / Mirko Tos, Per Leganger Larsen r / Birgit Winther, Jack M. Gwaltney, Jr. r / Dean M. Clerico r / David M. Yousem r / Dean M. Clerico r / Hun-Jong Dhong, Donald C. Lanza r / David W. Kennedy r / Hiroshi Moriyama r / Rodney P. Lusk r / Frederick A. Kuhn r / Ralph Metson r / Douglas E. Mattox, Mark Loury r / Elie E. Rebeiz, Stanley M. Shapshay r / William Lawson, Anthony J. Reino r / William H. Friedman r
Includes bibliographical references and index.
Keywords: Paranasal sinuses -- Diseases; Paranasal Sinus Diseases -- surgery; Paranasal Sinus Diseases; Paranasal Sinuses